Acute onset budd-chiari syndrome in the postpartum period - Unnati Bhatia; Mruthunjaya D Hulgur; Jennifer Hannigan; Arul Nallapillai (Wolters Kluwer Medknow Publications, 2023)
Budd-Chiari syndrome, though rare, can have devastating consequences during pregnancy. The presence of varied anatomical and physiological changes in pregnancy can worsen this condition. Owing to the rarity of this condition, the understanding of this disease process is limited and still evolving. Due to the acute clinical manifestations, it would be prudent to keep a close watch on women with hepatic vascular events in the peripartum period. We describe the anesthetic management of a primigravida who suddenly deteriorated in the immediate postpartum period following an uneventful forceps delivery with a high vaginal tear repair under spinal anesthesia. The challenges faced, including difficulty in establishing a diagnosis, have been discussed.